Native Rhizobia Strains Enhance Seed Yield of Groundnut Varieties in Northern Ghana - Wilson, Godfre; Ulzen, Jacob; Abaidoo, Robert Clement; Opoku, Andrews; Adjei-Nsiah, Samuel; Osei, Ophelia (Frontiers in Agronomy, 2021)
Rhizobia inoculation with effective isolates is an environmentally friendly approach for enhancing nodulation and yield of legumes. To obtain an ideal strain for inoculant production, the strain's performance must be matched to the environmental conditions. A 2 × 9 cross factorial experiment laid in randomized complete block design with three replications on farmers’ fields in the northern part of Ghana was set up to evaluate the rhizobia’s performance. The factors were groundnut varieties (Chinese and Samnut 22) and nine strains consisting of five native rhizobia strains (KNUST 1001, 1002, 1003, 1032 and 1031), two commercial strains (Biofix and BR3267), a positive (N+) and absolute control (N-). In addition, the population of the strains was assessed after a cropping season. The strains performance on groundnut were location and variety dependent. At Cheshegu, KNUST 1031 and KNUST 1002 significantly increased the seed yield of Chinese compared to other strains, however, KNUST 1031 elicited a 24% yield increase while KNUST 1002 caused a 16% yield increase over the control. The strain KNUST 1031 increased seed yield of Chinese by 24% while KNUST 1002 increased seed yield of Samnut by 16%. Only KNUST 1002 elicited a significant seed yield increase in Samnut 22 at Cheshegu. At Binduri, strain KNUST 1003 significantly increased seed yield of Chinese by 35% relative to the control. The Samnut 22 did not show a clear preference for any of the strains. Chinese variety did not show a clear response to the strains at Tanina. However, Samnut 22 responded to KNUST 1002 as it increased seed yield by 45% relative to the control. On average, the seed yield at Tanina (846.15 kg ha-1) was less than the seed yield recorded at Binduri (1077.66 kg ha-1) and Cheshegu (1502.78 kg ha-1). Inoculation with strains KNUST 1002, 1003, and 1031 were all profitable under the current experimental conditions as they recorded VCRs above the threshold of 3-4. The study has shown that strains, KNUST 1002, 1003 and 1031 have the potential to be used in inoculant formulation to increase groundnut production and enhance the income of smallholder groundnut farmers in northern Ghana.